2022
DOI: 10.1002/cbic.202200320
|View full text |Cite
|
Sign up to set email alerts
|

AIEgens Based on Anion‐π+ Interactions: Design, Synthesis, Photophysical Properties, and Their Applications in Material Science and Biology

Abstract: The design of novel aggregation‐induced emission luminogens (AIEgens), has generally been facilitated by disrupting the possibility of π‐π stacking. The recent literature describes a novel strategy to design AIEgens by introducing anion‐π+ interactions to prevent the detrimental π‐π stacking. This new strategy provides access to intrinsically charged AIEgens whose photophysical properties can be tuned either by incorporating different substituents on the π‐molecular scaffold to modulate the acidity for tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…10 Taken together, the published reviews are discrete and provide the impression that the field of gold catalysis has limited applications in the development of MCRs. Based on our continuing interest in the field of gold catalysis 11 and inspired by our recent work on gold-catalyzed MCRs, 12 we endeavoured to scrutinize all the available literature reports carefully. The literature survey revealed that there exist numerous gold-catalyzed MCRs with interesting reactivity patterns.…”
Section: Multicomponent Reactions – An Overviewmentioning
confidence: 99%
“…10 Taken together, the published reviews are discrete and provide the impression that the field of gold catalysis has limited applications in the development of MCRs. Based on our continuing interest in the field of gold catalysis 11 and inspired by our recent work on gold-catalyzed MCRs, 12 we endeavoured to scrutinize all the available literature reports carefully. The literature survey revealed that there exist numerous gold-catalyzed MCRs with interesting reactivity patterns.…”
Section: Multicomponent Reactions – An Overviewmentioning
confidence: 99%
“…37 Recent progress has been summarized in the reviews. 38,39 So far, studies of AIEgens based on anion-π interactions have mainly focused on fluorescent small molecules, 31 whereas research into phosphorescent materials has been rarely reported. Cationic iridium(III) complexes are well known as efficient triplet state luminescent materials with unique photophysical properties, including relatively short excitedstate lifetimes, excellent photo-and thermal stabilities, tunable emission properties, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Non-covalent interactions, such as hydrogen-bonding, π–π, and electron donor–acceptor interactions, play crucial roles in molecular self-assembly. Among these non-covalent interactions, anion−π interactions have aroused great interest lately. In a broad sense, anion−π interactions are interactions between anions and electron-deficient aromatic rings. , Not only new sensing methods but also tools for modulating molecular arrangement to produce desired optoelectronic character have been developed. Its applications have also been extended to the catalytic field.…”
mentioning
confidence: 99%